Analisis Rantai Pasok Cabai Merah di Kabupaten Garut - Alam, Agum Restu; Wulandari, Eliana; Widadie, Fanny (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The chili supply chain is a complex system that involves various stages from production at the farm level to distribution and consumption by the community. This process includes a series of interrelated activities, such as planting, harvesting, packaging, transportation, storage, and selling in traditional and modern markets. This study aims to analyze the supply chain (product flow, financial flow, and information flow) of red chili in Cikajang SubDistrict, Garut District. This research uses qualitative design. Data analysis used in the supply chain is qualitative descriptive. The results showed that the supply chain structure involves farmers, collectors and distributors. The flow of products goes from farmers to collectors and then to distributors, supported by cash or delayed payment mechanisms that are influenced by quality, quantity, and market conditions. The flow of information takes place directly between actors, although informal communication is still dominant. The main challenges faced are price fluctuations, delayed payments, and lack of transparency in information and financial flows. Integration and strengthening of supply chain management is needed to improve the efficiency, transparency, and competitiveness of red chili in this area.